ОҚЫТЫЎШЫ – ОҚЫЎШЫ – ШАҢАРАҚТЫҢ ӨЗ АРА ҚАРЫМ – ҚАТНАСЫ БОЙЫНША МӘСЛӘҲӘТ БЕРИЎ МАШҚАЛАЛАРЫ - Клычева, З.П. (ILIM hám JÁMIYET, 2017)
The article deals with actual issues of consultation on relations of teacher, pupils, family on questions of psychological development, teaching and education of children. It gives the information about characteristics of age individual features of their cognitive activity, social development, education of emotional qualities of the person. Questions of the diagnostic work are also analyzed in the article.